PENGEMBANGAN MODUL AJAR BERBASIS WEB MENGGUNAKAN GOOGLE SITES PADA MATERI PERILAKU KONSUMEN KELAS X BISNIS DIGITAL SMKN 4 SURABAYA - Dinda Melati Putri; Finisica Dwijayati Patrikha (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
The rapid development of information technology demands the education sector to continuously innovate in delivering learning materials. This study aims to develop a web-based learning module to improve students' learning outcomes using the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The research subjects were students of class X Digital Business 1 at SMKN 4 Surabaya. The research instruments included expert validation by subject matter experts, media experts, and language experts, as well as student responses collected through questionnaires. Data analysis was carried out using descriptive qualitative and quantitative methods. The result of this study is a web-based learning module using Google Sites on consumer behavior material. The product feasibility received a "very feasible" rating from subject matter experts (88%), media experts (92%), and language experts (92%). Student responses to the module were very positive, with a score of 91%. The N-Gain score of 0.7 indicates that the module is easy to understand, engaging, and capable of improving students' comprehension.